2012
DOI: 10.1007/s00125-012-2758-z
|View full text |Cite
|
Sign up to set email alerts
|

The human L-type calcium channel Cav1.3 regulates insulin release and polymorphisms in CACNA1D associate with type 2 diabetes

Abstract: Aims/hypothesis Voltage-gated calcium channels of the L-type have been shown to be essential for rodent pancreatic beta cell function, but data about their presence and regulation in humans are incomplete. We therefore sought to elucidate which L-type channel isoform is functionally important and its association with inherited diabetes-related phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…In addition, the increase in [Ca 2+ ] i acts as a stimulus for CICR from the ER through ryanodine receptors (RyRs). ER-released Ca 2+ is an agonist of the inositol 1,4,5-triphosphate receptor (IP3R) and stimulates additional Ca 2+ release from IP3R-regulated Ca 2+ stores; RyR-and IP3R-mediated Ca 2+ release is facilitated by the PKA signaling pathway (3,47). As a result, increases in insulin biosynthesis and exocytosis cause enhanced insulin secretion, and the PKA and Epac signaling pathways serve different roles in the process of GSIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase in [Ca 2+ ] i acts as a stimulus for CICR from the ER through ryanodine receptors (RyRs). ER-released Ca 2+ is an agonist of the inositol 1,4,5-triphosphate receptor (IP3R) and stimulates additional Ca 2+ release from IP3R-regulated Ca 2+ stores; RyR-and IP3R-mediated Ca 2+ release is facilitated by the PKA signaling pathway (3,47). As a result, increases in insulin biosynthesis and exocytosis cause enhanced insulin secretion, and the PKA and Epac signaling pathways serve different roles in the process of GSIS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the Ca 2+ channels known to be on the cell surface membranes of β-cells include voltage-dependent Ca 2+ channels (VDCCs), including Cav1.2 and Cav1.3, the Ca 2+ release-activated channel (CRAC) and transient receptor potential (TRP) family channels. A previous study revealed that Cav1.3 is associated with the regulation of insulin secretion in β-cells (3). The CRAC channel on the cell surface membrane of β-cells is activated by the release of Ca 2+ from the ER; this channel replenishes the ER with Ca 2+ , and mediates ER-regulated membrane potential and insulin secretion (4).…”
Section: +mentioning
confidence: 99%
“…For example, human betacell expression of CACNA1D mRNA exceeds CACNA1C mRNA by 60 times (Reinbothe et al, 2013). Although the same predominance of Cav1.3 is observed in the rat, in the mouse, Cav1.2 channels are dominant (Hiriart and AguilarBryan, 2008;Rorsman et al, 2012).…”
Section: Downloaded Frommentioning
confidence: 92%
“…This effect could impair insulin exocytosis, because release-competent granules may not be exposed to exocytotic local levels of Ca 21 (Rorsman et al, 2012). Furthermore, two single-nucleotide polymorphisms in the CACNA1D gene (Cav1.3) reduce its mRNA expression, impair insulin secretion, and are associated with type 2 diabetes (Reinbothe et al, 2013). Finally, blocking L-type calcium channels with diazoxide could inhibit hyperglycemia-induced beta-cell apoptosis .…”
Section: The Role Of Cav Channels In the Pathophysiology Of Ms And T2dmmentioning
confidence: 99%
“…Our mutant mouse expresses only SNAP-25a, and thus those excitable cells that normally express SNAP-25b in the exocytosis process are affected (23,25,26,59). In this respect, it is intriguing that several genes identified in GWAS or in functional studies as carrying a risk for susceptibility for T2D encode proteins that are important for insulin secretion from β cells, including potassium channels, voltage-gated Ca 2+ channels, and G protein-coupled receptors (34)(35)(36)(37)(38). These genes also are expressed in other excitable cells, including neurons, and therefore it is possible to envisage a scenario similar to that of our SNAP-25b-deficient mice in which a small imbalance in stimulus-dependent exocytosis mechanisms in excitable cells deregulates the interplay of metabolic signals and is followed by obesity and T2D.…”
Section: (E and F) Hypothalamic Pstat3 Is Decreased In All Experimentmentioning
confidence: 99%